1999
DOI: 10.1063/1.125269
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature coercivity enhancement in mechanically alloyed antiferromagnetic-ferromagnetic powders

Abstract: The coercivity, HC, and squareness of Co powders have been enhanced at room temperature by mechanically alloying them with antiferromagnetic powders with Néel temperature, TN, above room temperature. The enhancement is maximum after field annealing above TN. The existence of loop shifts and the dependence of HC on the annealing and measuring temperatures indicate that exchange bias effects are responsible for this behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 22 publications
2
74
0
Order By: Relevance
“…However, in most of the cases theories were limited to specific problems where intricate structures at the interfaces were simplified. Until now, EB effects have been exploited in several technological applications such as read head of recording devices [39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54], magnetoresistive random access memories (MRRAM) [55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76] and it has been proposed for the technological applications in stabilizing magnetization of superparamagnetic nanoparticles [77,78,79,80] or to improve coercivity and energy product of the permanent magnets [81,82,83,84].…”
Section: Introductionmentioning
confidence: 99%
“…However, in most of the cases theories were limited to specific problems where intricate structures at the interfaces were simplified. Until now, EB effects have been exploited in several technological applications such as read head of recording devices [39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54], magnetoresistive random access memories (MRRAM) [55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76] and it has been proposed for the technological applications in stabilizing magnetization of superparamagnetic nanoparticles [77,78,79,80] or to improve coercivity and energy product of the permanent magnets [81,82,83,84].…”
Section: Introductionmentioning
confidence: 99%
“…Though various efforts were made earlier to enhance the blocking temperature using exchange bias [20,21], the present work deals with the lower particle sizes of a few…”
Section: From the Fc And Zfc Magnetization (M) Vs Temperature(t) Curvmentioning
confidence: 99%
“…While they achieve a high interface/volume ratio, core-shell nanoparticles and thin film architectures do not result in large quantities of exchange-biased material. As an alternative, novel methods of processing exchange biased systems have been explored, including coevaporation, 8 mechanical milling, 9 and spontaneous phase separation. 14 have demonstrated that remarkable microstructures with aligned porosity can be observed when the reduction product shares a common oxygen sublattice with the precursor.…”
Section: Introductionmentioning
confidence: 99%